Pesantren Sebagai Solusi Pemberdayaan Ekonomi Kerakyatan - Arif Rahman Nurul Amin; Maya Panorama (CV. Syntax Corporation Indonesia, 2021)
Islamic boarding schools are religious institutions engaged in education, as well as developing and disseminating Islamic religious knowledge and da'wah, making Islamic boarding schools have a function as a center for religious thinkers. Islamic boarding schools also have a function as an institution that prints human resources, and as an institution that has the power to empower the alumni of the pesantren family and the surrounding community. This study seeks to explore data to find the basics of phenomena, reality and experience, which aims to provide a variety of knowledge treasures on how to optimize pesantren-based economic empowerment. Economic empowerment is both a process and a goal. As a process, economic empowerment is a series of activities to strengthen the power or empowerment of weak groups (economic conditions) in society. As a goal, empowerment refers to the state or result to be achieved, and the concept of the goal of empowerment is often used as an indicator of the success of empowerment as a process. Things that support the realization of empowerment such as; the existence of religious doctrines, the role of santri in empowerment, strengthening the pesantren-based populist economy, then as a concrete and applicable step the implementation of populist economic empowerment must pay attention to 3 main things, namely production potential, distribution potential, and consumption potential. The potential contribution of pesantren to improving the people's economy cannot be denied, Islamic boarding schools with all their historical and cultural dynamics have an important role in nationality, so that with quantity and quality pesantren can contribute and play an important role in empowering the people's economy.